2010
DOI: 10.1302/0301-620x.92b3.22592
|View full text |Cite
|
Sign up to set email alerts
|

Increased strain in the femoral neck following insertion of a resurfacing femoral prosthesis

Abstract: The cortical strains on the femoral neck and proximal femur were measured before and after implantation of a resurfacing femoral component in 13 femurs from human cadavers. These were loaded into a hip simulator for single-leg stance and stair-climbing. After resurfacing, the mean tensile strain increased by 15% (95% confidence interval (CI) 6 to 24, p = 0.003) on the lateral femoral neck and the mean compressive strain increased by 11% (95% CI 5 to 17, p = 0.002) on the medial femoral neck during stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
(68 reference statements)
1
8
0
Order By: Relevance
“…Our laboratory has traditionally used fresh frozen femurs for biomechanical experiments (Aamodt et al 2001, Wik et al 2010) and fresh frozen femurs were chosen accordingly. During the course of our study embalmed femurs were shown to provide similar mechanical properties to fresh frozen ones and could have been an alternative (Topp et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has traditionally used fresh frozen femurs for biomechanical experiments (Aamodt et al 2001, Wik et al 2010) and fresh frozen femurs were chosen accordingly. During the course of our study embalmed femurs were shown to provide similar mechanical properties to fresh frozen ones and could have been an alternative (Topp et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Hip resurfacing offers the potential advantage of loading the femoral neck and proximal femur thus avoiding stress shielding and bone resorption. However, hip resurfacing also leads to increases in femoral neck strain which may contribute to neck fractures [21]. Neck thinning and bone resorption under the femoral component is observed in hip resurfacing in, between 77 to 98% of cases [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…These two stems ( Figure 10 and sixteen male and six females (Table 1). The femurs were handled and prepared according to a previously described and documented procedure (125)(126)(127). The femurs were wrapped in saline-soaked towels and stored at -80°C immediately after dissection.…”
Section: Paper IVmentioning
confidence: 99%
“…hip simulator consists of a hip jig powered by a servohydraulic MTS MiniBionix II. The geometrical specifications were defined according to McLeish and Charnley(34), and the method has been standardized and evaluated at the Orthopaedic Research Centre of Trondheim University Hospital(125)(126)(127)129).During this project, the simulator has gained some improvements due to the moving of the biomechanical laboratory to new facilities. The design and base of the hip jig was the same, but a new supporting frame was added.…”
mentioning
confidence: 99%